A pulse modulatable self-oscillation kinetics for water oxidation at large current on manganese catalyst. (20th March 2020) - Zhou, Huang; Zhang, Nannan; Bai, Hui; Ming, Hai; Zhang, Qin; Du, Jun; Fan, Xing; Tao, Changyuan
Abstract: As a common obstacle for promoting water oxidation efficiency during the fast-charging of batteries or the industrial fuel production, it is in urgent need to clarify the unclear kinetics for the serious efficiency decline or decomposition of catalysis at a large current of >1000 A/m 2 . In this work, the intensified contribution of a kinetic pathway at large current to the water oxidation process on manganese catalyst was revealed. This pathway was proposed and verified by the observation of the periodic electrochemical self-oscillation, which can be modulated by external electrical pulse with different amplitude and frequency. At an external pulse with an average current of 0.08 A/cm 2 and a frequency of 130 Hz, the intrinsic self-oscillation can result in ∼14.6% reduction of power consumption. The kinetic role of peroxide and Mn(III) intermediates in this pathway was also analyzed, in order to provide both a mechanism insight and possible energy-saving strategies for industrial process.